The role of work–family role integration in a job demands–resources model among Chinese secondary school teachers. Issue 4 (15th June 2015) - Liu, Huimin; Cheung, Fanny M.
<x xml:space="preserve">Abstract</x> The current study examines an integrative demands–resources model of the work–family interface in a sample of 259 Chinese secondary school teachers. Participants completed questionnaires relating to job demands, job resources, work‐to‐family conflict, work‐to‐family enrichment, work–family role integration (WFRI) and burnout scale. Results show that: (i) job demands were strongly and positively associated with work‐to‐family conflict, which further led to an increase in burnout; job resources were strongly and positively associated with work‐to‐family enrichment, and consequently to a decrease in burnout. Job demands also had a significant direct impact on burnout; (ii) a newly proposed construct, WFRI, was found to partially mediate the relationship between job demands and work‐to‐family conflict, as well as between job resources and work‐to‐family enrichment. Theoretical and practical implications are discussed, and future research directions are provided.